2017
DOI: 10.1097/id.0000000000000484
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Postextraction Sites With Allograft-Stabilized Dental Implants

Abstract: Rehabilitation of wide postextraction defects may achieve successful outcomes using allograft and a special implant design, even in the absence of optimal primary stability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 52 publications
1
5
0
Order By: Relevance
“…Reason for Exclusion Aghazadeh et al, 2012 [140] Application of granular autograft Arenaz-Búa et al, 2010 [141] Application of granular autograft Barboza et al, 2010 [142] Application of allogeneic bone granules Beitlitum et al, 2018 [143] Application of allogeneic bone granules Bianconi et al, 2017 [144] Alveolar ridge preservation Charde et al, 2020 [145] Block used for peri-implant bone regeneration Naishlos et al, 2021 [146] Blocks used for sinus floor augmentation Corinaldesi et al, 2009 [147] Application of autogenous bone granules El Chaar et al, 2019 [148] Application of allogeneic bone granules Ge et al, 2017 [149] Application of granular autograft Güven and Tekin, 2006 [150] Wrong indication (cyst filling) Huang et al, 2016 [151] Application of allogeneic bone granules Ilankovan et al, 1998 [152] No outcome of interest reported Jacotti et al, 2012 [153] Sample size too small Kang et al, 2015 [154] Particulated iliac bone applied with sinus lift Khoury and Hanser, 2015 [155] No outcome of interest reported Krasny et al, 2018 [156] Inclusion of patients with follow-up of less than 12 months Lekholm et al, 1999 [157] Application of different surgical approaches, missing patient information [160] Application of granular materials Merli et al, 2020 [161] Application of granular grafting materials Morad and Khojasteh, 2013 [162] Sample size too small Mordenfeld et al, 2017 [163] Application of granular autograft Özkan et al, 2007 [164] Sample size too small Pimentel et al, 2014 [165] Sample size too small Putters et al, 2018 [166] No outcome of interest reported Quereshy et al, 2010 [167] Sample size too small Sethi et al, 2020 [168] Inclusion of patients with follow-up < 12 months Simion et al, 2001 [169] Application of granular materials Simon et al, 2000 [170] Surgical technique (ARP) Soehardi et al, 2009 [171] No differentiation between onlay block and sinus floor elevation Solakoglu et al, 2019 …”
Section: Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Reason for Exclusion Aghazadeh et al, 2012 [140] Application of granular autograft Arenaz-Búa et al, 2010 [141] Application of granular autograft Barboza et al, 2010 [142] Application of allogeneic bone granules Beitlitum et al, 2018 [143] Application of allogeneic bone granules Bianconi et al, 2017 [144] Alveolar ridge preservation Charde et al, 2020 [145] Block used for peri-implant bone regeneration Naishlos et al, 2021 [146] Blocks used for sinus floor augmentation Corinaldesi et al, 2009 [147] Application of autogenous bone granules El Chaar et al, 2019 [148] Application of allogeneic bone granules Ge et al, 2017 [149] Application of granular autograft Güven and Tekin, 2006 [150] Wrong indication (cyst filling) Huang et al, 2016 [151] Application of allogeneic bone granules Ilankovan et al, 1998 [152] No outcome of interest reported Jacotti et al, 2012 [153] Sample size too small Kang et al, 2015 [154] Particulated iliac bone applied with sinus lift Khoury and Hanser, 2015 [155] No outcome of interest reported Krasny et al, 2018 [156] Inclusion of patients with follow-up of less than 12 months Lekholm et al, 1999 [157] Application of different surgical approaches, missing patient information [160] Application of granular materials Merli et al, 2020 [161] Application of granular grafting materials Morad and Khojasteh, 2013 [162] Sample size too small Mordenfeld et al, 2017 [163] Application of granular autograft Özkan et al, 2007 [164] Sample size too small Pimentel et al, 2014 [165] Sample size too small Putters et al, 2018 [166] No outcome of interest reported Quereshy et al, 2010 [167] Sample size too small Sethi et al, 2020 [168] Inclusion of patients with follow-up < 12 months Simion et al, 2001 [169] Application of granular materials Simon et al, 2000 [170] Surgical technique (ARP) Soehardi et al, 2009 [171] No differentiation between onlay block and sinus floor elevation Solakoglu et al, 2019 …”
Section: Studymentioning
confidence: 99%
“…List of excluded studies with reasons for exclusion. Aghazadeh et al, 2012 [140] Application of granular autograft Arenaz-Búa et al, 2010 [141] Application of granular autograft Barboza et al, 2010 [142] Application of allogeneic bone granules Beitlitum et al, 2018 [143] Application of allogeneic bone granules Bianconi et al, 2017 [144] Alveolar ridge preservation Charde et al, 2020 [145] Block used for peri-implant bone regeneration Naishlos et al, 2021 [146] Blocks used for sinus floor augmentation Corinaldesi et al, 2009 [147] Application of autogenous bone granules El Chaar et al, 2019 [148] Application of allogeneic bone granules Ge et al, 2017 [149] Application of granular autograft Güven and Tekin, 2006 [150] Wrong indication (cyst filling) Huang et al, 2016 [151] Application of allogeneic bone granules Ilankovan et al, 1998 [152] No outcome of interest reported Jacotti et al, 2012 [153] Sample size too small Kang et al, 2015 [154] Particulated iliac bone applied with sinus lift Khoury and Hanser, 2015 [155] No outcome of interest reported Krasny et al, 2018 [156] Inclusion of patients with follow-up of less than 12 months Lekholm et al, 1999 [157] Application of different surgical approaches, missing patient information Lima et al, 2018 [158] Sample size too small…”
Section: Fundingmentioning
confidence: 99%
“…Since these cases often coincide with a reduced amount of keratinized tissue, the management of the membrane cover may become uncomfortable. For the above-mentioned reasons and in analogy with previous studies [40][41][42], further potential complications were avoided in the present study by allowing for the soft tissues to heal and early bone regeneration to take place at the apical part of the defect during the secondary closure after implant removal. For instance, a trabecular metal (TM) implant was inserted concomitantly with a GBR procedure two months after implant removal.…”
Section: Discussionmentioning
confidence: 92%
“…In previous studies, implants placed two months after tooth removal in wide postextraction defects, with less-than-optimal primary stability via compaction of a surrounding bone substitute, successfully osseointegrated for functional loading after five months [40,41]. The rationale of such an interval between tooth extraction and implant insertion was mainly to allow for soft tissue healing involving an adequate amount of keratinized tissue around the implant at placement.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental in vivo studies have shown that implants with rough surfaces that lacked or had no primary stability reached the same degree of osseointegration as those with high primary stability, given the appropriate healing time (Abdel-Haq, Karabuda, Arisan, Mutlu, & Kurkcu, 2011;Jung et al, 2012;Kim et al, 2014). A recent clinical case series study also showed that when implants were placed without contact in pristine bone, yet stabilized by allografts, acceptable osseointegration assessed by a reverse torque of more than 30 Ncm could be achieved after 5 months of healing time (Bianconi, Bozzoli, & Fabbro, 2017).…”
Section: Introductionmentioning
confidence: 99%